Non-observance of Conversational Maxims as a Source of Humour in the Sitcom The Big Bang Theory - Dančová, Markéta (Univerzita Pardubice, 2019)
The aim of this paper is to analyze the Maxim non-observance in the sitcom The Big Bang Theory, more specifically, how and when Maxim non-observance is used for creating humorous conversations. The theoretical part focuses on the work of H. P. Grice, the terms implicature, the Cooperative Principle, and Maxims of conversation are introduced. In the following chapters, humor is defined and linked to the non-observance of Maxims of conversation. The practical part focuses on analysis of selected conversations from the sitcom and tries to find the rules for using Maxim non-observance for creating humor.
Porušování konverzačních maxim za účelem humoru v sitcomu Teorie velkého třesku
Keywords: maxims of conversation; implicature; pragmatics; humor; sarcasm; sitcom; konverzační maximy; implikatura; pragmatika; humor; sarkasmus; sitkom